Pharmacoepidemiological Rationale for the Use of Antibacterial Agents in Community-Acquired Pneumonia in Children of Different Ages (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Community-acquired pneumonia in pediatric patients represents one of the most frequent and clinically significant infectious diseases worldwide. The necessity of antibacterial therapy is undisputed, yet the rationality of its use varies substantially depending on patient age, comorbidities, and regional resistance patterns. This study provides an expanded pharmacoepidemiological evaluation of antibacterial drug prescribing in children, aiming to compare real-world practices with evidence-based guidelines. The focus is placed on analyzing therapeutic strategies in neonates, infants, preschoolers, school-age children, and adolescents, thereby highlighting distinct prescribing patterns and their impact on treatment outcomes. By examining the correlation between drug selection, therapy duration, and clinical success rates, this research identifies critical gaps in current practices and provides insights into optimizing antibacterial therapy. Findings reveal that inappropriate empirical choices, frequent reliance on broad-spectrum antibiotics, and lack of age-adjusted dosing regimens are central issues undermining both treatment safety and long-term effectiveness. Pharmacoepidemiology emerges as a decisive tool in guiding rational prescription and ensuring sustainable antimicrobial use in pediatric medicine. Community-acquired pneumonia in children continues to represent one of the most pressing clinical and epidemiological challenges worldwide, demanding the rational use of antibacterial therapy across all age categories. The complexity of therapeutic decision-making arises from differences in pathogen prevalence, pharmacokinetics, and immunological maturity at different developmental stages. The current analysis highlights pharmacoepidemiological data concerning the choice, duration, and outcomes of antibacterial regimens, with emphasis on identifying both effective strategies and common errors that undermine long-term therapeutic success. The results reveal that while narrow-spectrum beta-lactams remain the cornerstone of therapy in younger children, there is widespread overreliance on macrolides and cephalosporins in older groups, often without bacteriological justification. Moreover, the inappropriate prescription of second-line agents contributes significantly to the development of resistance and exposes children to unnecessary adverse drug reactions. The study advocates for optimized antimicrobial stewardship strategies tailored to pediatric practice in order to align prescribing with international guidelines and preserve antibiotic efficacy for future generations.